The Impact of Maternal Prenatal Depressive Symptoms and Anxiety on Infant Birth Weight in Japanese Primiparous Women - Hitomi Kanekasu; Mayumi Nishioka; Shu Taira; Hiroko Watanabe (Women, Midwives and Midwifery, 2021)
Introduction: Depressive symptoms and anxiety are the most common mental health problems during pregnancy. The purpose of the present study was to investigate the association between each trimester’s maternal depressive symptoms, anxiety, and infant birth weight. Methods: We recruited pregnant women in their second trimester. Participants’ blood and saliva were collected in the second trimester to investigate plasma cortisol and saliva oxytocin levels. Participants completed self-reported questionnaires that included the Edinburgh Postnatal Depression Scale (EPDS) and the State-Trait Anxiety Inventory (STAI) in the second and third trimesters. Hierarchical multiple linear regression was conducted using stepwise selection. Results: Eighty-one primiparas participated in the study. As the results of linear regression showed, gestational age, hypertensive disorders of pregnancy, weight gain during pregnancy, and depressive symptoms in the third trimester were associated with infant birth weight. Depressive symptoms in the third trimester predicted lower infant birth weight. In contrast, depressive symptoms in the second trimester, state anxiety, and trait anxiety in both the second and third trimesters did not predict infant birth weight. Similarly, maternal plasma cortisol and saliva oxytocin levels were not related to infant birth weight. Conclusion: Maternal depressive symptoms in the third trimester predicted lower infant birth weight. Mental health care for depressive symptoms in late pregnancy might be important for infant birth weight increases.